Evaluation of Antimicrobial Activity of Balanites Roxburghii Planch Fruit Extracts - Kinjal H, Dr. Shah (International Journal of Scientific Research and Management (IJSRM), 2019)
Evaluation of antimicrobial activity was performed by cup-plate method. The test microorganisms used for the antimicrobial activity were four bacterial species (two Gram positive and two Gram negative) – Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeuroginosa,Escherichia coli. The test microorganisms used for the antimicrobial activity were four bacterial species (two Gram positive and two Gram negative) – Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeuroginosa, Escherichia coli.